2020
DOI: 10.1080/20016689.2020.1843277
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden of spinal muscular atrophy: an analysis of claims data

Abstract: Background: Spinal muscular atrophy (SMA) is a rare genetic neuromuscular disease. Objective: Characterize direct costs associated with SMA management. Data source: Truven Health Analytics MarketScan claims data (2012-2016). Patients: Eligible patients had ≥2 SMA-related medical claims ≥30 days apart. Patients were matched (1:1) to controls by birth year, gender, and geographic region. Patients were categorized as having infantile, child, or juvenile SMA based on diagnosis at age <1, 1-3, or 3-18 years, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 41 publications
3
13
0
Order By: Relevance
“…b Covering 49 unique studies; two full publications and two conference abstracts were linked studies; both have been retained in the current report as they each report unique relevant data. EBM evidence-based medicine reviews, SLR systematic literature review frequently reported separately for individuals with Type 1 (n = 11) [48,54,57,63,65,66,68,81,84,91,93]; Types 1-3 SMA (n = 11; each type reported separately [52,55,58,59,67,69,71,75,76,96,98]; Type 3 SMA including subgroups (n = 1) [82]; and adult patients with SMA (n = 1) [74] or were reported for a mixed population of individuals with SMA: infantile-onset and other SMA (excluding Type 4 SMA; n = 1) [79]; infantile-onset (≤ 7 years) and later-onset (2-12 years) SMA (n = 1) [61]; Type 1 SMA and other SMA (including Type 4 SMA; n = 2) [50,97]; early-onset SMA (patients with Types 1, 2 and 3 SMA aged ≤ 3 years); and other SMA (later-onset Types 2 and 3 SMA in addition to Type 4 SMA) [n = 1] [60]-reported separately for infantile-onset, childhood-onset and juvenile-onset SMA (n = 1) [70]; reported separately for patients with infantile-onset, childhood-onset and late-onset SMA (n = 1) [77]; a mixed population with Types 1, 2 and 3 SMA (n = 1) [95]; a mixed population with Types 2 and 3 SMA (n = 1) [64]; a mixed population with Types 2 and 3 SMA including subgroups (n = 1) [62]; a mixed population with Types 2 and 3 and unreported SMA type (n = 1) [88]; a mixed population with Types 1, 2, 3 and 4 SMA (n = 1) [73]; and a mixed population with SMA in whi...…”
Section: Description Of Identified Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…b Covering 49 unique studies; two full publications and two conference abstracts were linked studies; both have been retained in the current report as they each report unique relevant data. EBM evidence-based medicine reviews, SLR systematic literature review frequently reported separately for individuals with Type 1 (n = 11) [48,54,57,63,65,66,68,81,84,91,93]; Types 1-3 SMA (n = 11; each type reported separately [52,55,58,59,67,69,71,75,76,96,98]; Type 3 SMA including subgroups (n = 1) [82]; and adult patients with SMA (n = 1) [74] or were reported for a mixed population of individuals with SMA: infantile-onset and other SMA (excluding Type 4 SMA; n = 1) [79]; infantile-onset (≤ 7 years) and later-onset (2-12 years) SMA (n = 1) [61]; Type 1 SMA and other SMA (including Type 4 SMA; n = 2) [50,97]; early-onset SMA (patients with Types 1, 2 and 3 SMA aged ≤ 3 years); and other SMA (later-onset Types 2 and 3 SMA in addition to Type 4 SMA) [n = 1] [60]-reported separately for infantile-onset, childhood-onset and juvenile-onset SMA (n = 1) [70]; reported separately for patients with infantile-onset, childhood-onset and late-onset SMA (n = 1) [77]; a mixed population with Types 1, 2 and 3 SMA (n = 1) [95]; a mixed population with Types 2 and 3 SMA (n = 1) [64]; a mixed population with Types 2 and 3 SMA including subgroups (n = 1) [62]; a mixed population with Types 2 and 3 and unreported SMA type (n = 1) [88]; a mixed population with Types 1, 2, 3 and 4 SMA (n = 1) [73]; and a mixed population with SMA in whi...…”
Section: Description Of Identified Studiesmentioning
confidence: 99%
“…Cost drivers (factors that create or drive the cost of management) associated with SMA were reported in 28 studies [50, 53-61, 64, 68, 70-79, 83-85, 92, 94, 97]. Major cost drivers included the requirement for inpatient care (n = 22) [50, 53-56, 58, 60, 68, 70-74, 76-79, 84, 85, 92, 94, 97], use of outpatient services or specialist visits (n = 16) [50, 53-55, 58-60, 70-74, 76, 78, 84, 85], respiratory care (n = 10) [50,54,55,57,61,70,71,73,78,83], rehabilitation (n = 4) [50,55,79,97], orthopaedic care (n = 2) [61,83], prescription costs (excluding DMT-related costs) [n = 8] [50, 53,58,60,74,76,77,84], home stays (n = 3) [58,70,79] and structural changes to the house or car (n = 6) [55,59,60,64,71,75]. One study reported cost drivers to be type dependent, with Type 1 SMA costs driven by respiratory care, and Types 2 and 3 SMA costs driven by orthopaedic care [83].…”
Section: Cost Driversmentioning
confidence: 99%
See 1 more Smart Citation
“…SMA is another rare neurological disease with tremendous burdens for patients, their families, caregivers and society. Before the advent of novel drugs, the estimated annual outpatient cost for infantile SMA was approximately $55,538, while annualized inpatient cost was $100,000 per infantile SMA patient (113). Nusinersen costs $118,000 per vial and the annual cost of treatment with it ranges from $354,000 to $708,000 for the first year of the treatment (114).…”
Section: Spinal Muscular Atrophymentioning
confidence: 99%
“…Hence, SMA has a severe impact on the patient's quality of life (QoL) and life expectancy (Landfeldt et al, 2019). Apart from the clinical burden, SMA also places a significant economic burden, in particular on parents taking care of their child with SMA (Klug et al, 2016;López-Bastida et al, 2017;Belter et al, 2020).…”
Section: Introductionmentioning
confidence: 99%